Electronic and magnetic properties of the interface LaAlO 3 /TiO 2 anatase from density functional theory - Weissmann, Mariana Dorotea (2012)
Ab initio calculations using the local spin density approximation and also including the Hubbard U have been performed for three low-energy configurations of the interface between LaAlO 3 and TiO 2 anatase. Two types of interfaces have been considered: LaO/TiO 2 and AlO2/TiO, the latter with Ti termination and therefore a missing oxygen. A slab-geometry calculation was carried out, and all the atoms were allowed to relax in the direction normal to the interface. In all the cases considered, the interfacial Ti atom acquires a local magnetic moment, and its formal valence is less than +4. When there are oxygen vacancies, this valence decreases abruptly inside the anatase slab, while in the LaO/TiO 2 interface, the changes are more gradual.